Priming correct information reduces the misinformation effect. - Gordon, Leamarie; Shapiro, Amy (Memory & Cognition, 2012)
The misinformation effect is a well-established phenomenon in the false memory literature, although the mechanisms that underlie it are debated. In the present study, we explored one aspect of the controversy, the fate of the original memory. We began from an activation-based view of memory, capitalizing on the well-understood processes of associative priming and spreading activation, to test the hypothesis that true and suggested information can coexist in memory. After exposure to misinformation, participants were unknowingly primed with associates of either the true or a suggested item. Misled participants who were primed for the true item performed better on a final memory test than did misled participants primed for neutral information. The results indicated that true and suggested information coexist and that retrieval is influenced by each concept's activation level at test. Implications for theories of the misinformation effect were discussed.